Faktor-faktor yang Mempengaruhi Financial Distress Pada Perusahaan Manufaktur - Rifka Damayanti; Sri Hermuningsih; Ratih Kusumawardhani (J-MAS (Jurnal Manajemen dan Sains), 2021)
This study aims to determine the factors that influence financial distress in manufacturing companies in the goods and consumption industry sector. This research uses five variables, namely liquidity, leverage, profitability, firm growth as the dependent variable, and financial distress as the independent variable. The population in this study are manufacturing companies in the goods and consumption industry sector that have been listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period, amounting to 52 companies. The data collection method uses purposive sampling by using financial reports on manufacturing companies in the consumer goods and industrial sector. listed on the IDX in the 2015-2019 period. The results show that liquidity, leverage, profitability, and firm growth simultaneously affect financial distress in manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2019, liquidity has a significant effect on financial distress, leverage has no significant effect on financial distress, profitability has a significant effect on financial distress and firm growth have no significant effect on financial distress.